Antithrombotic activity of oral administered low molecular weight fucoidan from Laminaria Japonica. Issue 144 (August 2016) - Zhao, Xue; Guo, Fengjun; Hu, Jing; Zhang, Lijuan; Xue, Changhu; Zhang, Zhaohui; Li, Bafang
Abstract: Introduction: Fucoidans extracted from brown algae have been documented to have excellent antithrombotic activity when administered by either intravenous or subcutaneous route in animal models. However, it is unknown if the fucoidans also have antithrombotic activity when administered orally, a highly desirable feature of oral antithrombotic agents. In the present study, we compared the oral absorption, bioavailability and antithrombotic activity of two fucoidan fractions from Laminaria japonica with different molecular weight by oral administration in an electricity induced arterial thrombosis model and the underlying molecular mechanisms. Results and conclusions: After a single dose of oral administration, the fucoidan content in plasma and urine in rats was assessed using the reverse-phased HPLC analysis of 1-phenyl-3-methyl-5-pyrazolone (PMP)-labeled fucose. The fucose content in the low molecular weight (LMW) fucoidan-treated rats increased up to 2-fold and peaked at 15 h, indicating that the LMW fucoidan had much better absorption and bioavailability than the MMW fucoidan in vivo. Oral administration of the LMW fucoidan at 400 and 800 mg/kg for 30 days inhibited the arterial thrombosis formation effectively induced by electrical shock in rats, accompanied by moderate anticoagulation activity, regulation on TXB2 and 6-keto-PGF1α, significant antiplatelet activity and effective fibrinolysis. The LMW fucoidan showed better oral absorption and antithrombotic activity in addition to different antithrombotic mechanisms compared to those of the medium molecular weight (MMW) fucoidan. Thus, the LMW fucoidan has a potential to become an oral antithrombotic agent. Graphical abstract: Highlights: Reverse-phased HPLC method for fucoidan content analysis in blood and urine LMW fucoidan possessed higher absorption and bioavailability. Oral administration of LMW fucoidan exhibited excellent antithrombotic activity. Absorption played an important role on the antithrombotic activity of fucoidan.